Capacity Building in an Effort of Improving Blended Learning-Based Teacher' Competence during Covid-19 Pandemic - Ana Nurwakhidah; Asep Dadan Suganda (Tarbawi, 2022)
The purpose of this study is to find out the effectiveness of implementing capacity building for teachers during the COVID-19 pandemic on the basis of blended learning. This study used a descriptive qualitative approach. Data collection was obtained from informants and the behavior of people who were observed, interviewed, and documented as the primary data sources and the rest was secondary data from available document. The choice of this learning model is one of the decisions taken by considering situations and conditions that meet the learning model. However, since the teachers' competency in implementing blended learning were various in level, it is necessary to provide assistance in implementing blended learning through capacity building. Capacity building is a strategy to increase the effectiveness, responsiveness and efficiency of teachers’ performance in the context of blended learning. As lecturers have the obligation of the Tri Dharma of Higher Education, one of which is community service, lecturers can participate in mentoring blended learning through capacity building. The result of this study is that teachers already have online classes and can manage online classes and take care of classes using blended learning.